Development a flexible light‐sheet fluorescence microscope for high‐speed 3D imaging of calcium dynamics and 3D imaging of cellular microstructure. Issue 6 (12th March 2020) - Sparks, Hugh; Dvinskikh, Liuba; Firth, Jahn M.; Francis, Alice J.; Harding, Sian E.; Paterson, Carl; MacLeod, Ken T.; Dunsby, Chris
Abstract: We report a flexible light‐sheet fluorescence microscope (LSFM) designed for studying dynamic events in cardiac tissue at high speed in 3D and the correlation of these events to cell microstructure. The system employs two illumination‐detection modes: the first uses angle‐dithering of a Gaussian light sheet combined with remote refocusing of the detection plane for video‐rate volumetric imaging; the second combines digitally‐scanned light‐sheet illumination with an axially‐swept light‐sheet waist and stage‐scanned acquisition for improved axial resolution compared to the first mode. We present a characterisation of the spatial resolution of the system in both modes. The first illumination‐detection mode achieves dual spectral‐channel imaging at 25 volumes per second with 1024 × 200 × 50 voxel volumes and is demonstrated by time‐lapse imaging of calcium dynamics in a live cardiomyocyte. The second illumination‐detection mode is demonstrated through the acquisition of a higher spatial resolution structural map of the t‐tubule network in a fixed cardiomyocyte cell. Abstract : We report a flexible light‐sheet fluorescence microscope (LSFM) designed for studying dynamic events in cardiac tissue at high speed in 3D and the correlation of these events to cell microstructure. The system employs two illumination‐detection modes: the first uses angle‐dithering of a Gaussian light sheet combined with remote refocusing of the detection plane for video‐rate volumetric imaging; the second combines digitally‐scanned light‐sheet illumination with an axially‐swept light‐sheet waist and stage‐scanned acquisition for improved axial resolution compared to the first mode.